Fixed point theorems in metric spaces and probabilistic metric spaces - Yeol Je Cho; Keun Saeng Park; Shih-Sen Chang (International Journal of Mathematics and Mathematical Sciences)
In this paper, we prove some common fixed point theorems for compatible mappings of type (A) in metric spaces and probabilistic metric spaces Also, we extend Caristi's fixed point theorem and Ekeland's variational principle in metric spaces to probabilistic metric spaces.